2002
DOI: 10.1038/sj.bjp.0704622
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inducing divergent shifts of constitutive activity reveal different modes of binding among catecholamine analogues to the β2‐adrenergic receptor

Abstract: 1 We compared the changes in binding energy generated by two mutations that shift in divergent directions the constitutive activity of the human b 2 adrenergic receptor (b 2 AR). 2 A constitutively activating mutant (CAM) and the double alanine replacement (AA mutant) of catechol-binding serines (S204A, S207A) in helix 5 were stably expressed in CHO cell lines, and used to measure the binding a nities of more than 40 adrenergic ligands. Moreover, the e cacy of the same group of compounds was determined as intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 13 publications
7
36
0
Order By: Relevance
“…Norepi for G protein signaling ( Fig. 2A), which is consistent with previous studies for these compounds (January et al, 1998;Del Carmine et al, 2002;Baker, 2005;Moore et al, 2007). Next, we measured b2-AR internalization as the loss of cell surface receptors after agonist exposure using flow cytometry in cell expressing a flag-tagged receptor.…”
Section: Pronounced Differences In Upstream Cellularsupporting
confidence: 88%
“…Norepi for G protein signaling ( Fig. 2A), which is consistent with previous studies for these compounds (January et al, 1998;Del Carmine et al, 2002;Baker, 2005;Moore et al, 2007). Next, we measured b2-AR internalization as the loss of cell surface receptors after agonist exposure using flow cytometry in cell expressing a flag-tagged receptor.…”
Section: Pronounced Differences In Upstream Cellularsupporting
confidence: 88%
“…As reported for CXCR4, substitution of critical residues with different amino acids was associated with different levels of G protein coupling in mammalian cells (28). Moreover, some CAMs had ligand binding similar to the wild-type receptor, whereas others had decreased ligand affinities, indicative of shifts in the conformation of extracellular domains involved in binding sites (47). The CXCR4-CAMs were found to be phosphorylated and chronically desensitized while AT 1A -CAM had a basal level of phosphorylation similar to WT receptor even upon ligand stimulation (28,48).…”
Section: Discussionmentioning
confidence: 60%
“…In the work by Del Carmine et al (2002), it was found that mutations of residues within the putative binding pocket of the ␤2-adrenoceptor (S204,207A, predicted to project adjacent to our S219H mutation in the CCK-2R) decreased ligand affinities by shifting the receptor toward a less active conformation. For a subset of compounds that was investigated, the latter effect (i.e., loss of affinity secondary to a shift in receptor conformation) seemed to be superimposed with a mutation-induced disruption of direct receptor-ligand interactions.…”
Section: Ligand Function At Constitutively Active Receptor Mutants 757mentioning
confidence: 71%